2019
DOI: 10.1055/s-0039-1696702
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Peroperative Risk Factors Associated with Posttonsillectomy Reactionary Hemorrhage in a Teaching Hospital

Abstract: Introduction  Tonsillectomy is one of the most common otolaryngology procedures performed worldwide. It is also one of the first procedures learnt by residents during their training period. Although tonsillectomy is viewed relatively as a low-risk procedure, it can be potentially harmful because of the chance of posttonsillectomy hemorrhage. Objective  The objective of the present study is to analyze the effects of peroperative factors and experience of the surgeon on the incidence and pattern of posttonsille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Several authors have reported that the risk of post-tonsillectomy bleeding depends on the skill level of the surgeon, with the risk of bleeding increasing when procedures are performed by trainees. 10,26 In the current study, there was no association between the surgeon’s skill level and post-tonsillectomy bleeding which in keeping with other previous studies. 9,31 However, a surgeon’s inexperience and dissection in the wrong plane results in more post-tonsillectomy bleeding.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Several authors have reported that the risk of post-tonsillectomy bleeding depends on the skill level of the surgeon, with the risk of bleeding increasing when procedures are performed by trainees. 10,26 In the current study, there was no association between the surgeon’s skill level and post-tonsillectomy bleeding which in keeping with other previous studies. 9,31 However, a surgeon’s inexperience and dissection in the wrong plane results in more post-tonsillectomy bleeding.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the operation time is increased, leading to a greater loss of blood. 10 In present study, post-tonsillectomy bleeding was not found to be significant correlated with comorbidity, syndrome, or the history of recurrent tonsillitis which in line with other previous study. 32 No previous studies have found an impact of syndromes on postoperative bleeding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Post-tonsillectomy haemorrhage (PTH) has been considered one of the potentially life-threatening complications an ENT surgeon might face during surgical practice. 8 Tonsillectomy is one of the initial procedures learnt by the beginners, and although viewed as a relatively low-risk procedure, it can be potentially harmful because of the chance of post-tonsillectomy haemorrhage. 8 In a study done at Dhulikhel Hospital of Nepal, PTH was seen in 12.6% with one out of 15 PTH returning to the operation theatre.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Tonsillectomy is one of the initial procedures learnt by the beginners, and although viewed as a relatively low-risk procedure, it can be potentially harmful because of the chance of post-tonsillectomy haemorrhage. 8 In a study done at Dhulikhel Hospital of Nepal, PTH was seen in 12.6% with one out of 15 PTH returning to the operation theatre. 9 In the studies conducted in different centres and countries, the PTH varies from 3.3% to 13.9%.…”
Section: Discussionmentioning
confidence: 99%